2015
DOI: 10.1260/2040-2295.6.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Backrest Shape Affects Head–Neck Alignment and Seated Pressure

Abstract: Unstable back support against gravity results in a forward head posture and contributes to buttocks pressure ulcers. However, the association between these health problems and a wheelchair backrest is unclear. Our newly developed wheelchair (N-WC) supports the back of the pelvis and thorax from obliquely underneath. The purpose of this study was to investigate the effect of different backrest shapes on head-neck alignment and seated pressure. Data from 28 healthy subjects were analyzed. Outcome measures were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…On P-WC, upright head-neck alignment and backward inclination of the trunk were observed. This supports the results of a previous study that the new P-WC eliminated a forward head posture and expanded cervical movement [29,30]. From a kinematic perspective, the mass of the head, neck, and trunk accounts for 64.4% of total body weight [50], and this mass is positioned forward relative to the spine when seated upright.…”
Section: Measured Variablessupporting
confidence: 89%
See 1 more Smart Citation
“…On P-WC, upright head-neck alignment and backward inclination of the trunk were observed. This supports the results of a previous study that the new P-WC eliminated a forward head posture and expanded cervical movement [29,30]. From a kinematic perspective, the mass of the head, neck, and trunk accounts for 64.4% of total body weight [50], and this mass is positioned forward relative to the spine when seated upright.…”
Section: Measured Variablessupporting
confidence: 89%
“…The backrest of P-WC effectively promotes upright alignment of the head and neck in healthy individuals and the elderly [29,30]. However, the P-WC's potential to correct asymmetrical posture in patients with hemiparesis has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding preactive sitting posture, on the BS plane, the contact area between the wheelchair and patient, including the PL part, was increased and the COP was located nearer to the center of the supporting surface in P-WC than in C-WC. These results support the outcomes of our previous studies involving both stroke patients and healthy adults in static experiments [25,26]. The P-WC BS post is inclined backward in three stages, with a 100˚-wide angle design in the PL region as compared with a 96˚-wide angle design in C-WC.…”
Section: Plos Onesupporting
confidence: 89%
“…Focusing on the shape of C-WC, a previous study suggested that the contact area between the wheelchair and back (i.e., trunk including pelvis) was poor both in stroke patients and healthy adults [25,26]. The pelvis is the foundation of sitting posture and affects trunk positioning and lumbar and cervical spine alignment [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The back support of the standard type wheelchair comprises two parallel rods and a flat cover, which does not support individuals with kyphosis. As the trunk is pushed forward, these individuals exhibited a Forward Head Posture [2][3][4]. FHP not only fatigues the erector spinae muscle but also increases the integrated muscle activity of the suprahyoid muscle during swallowing [5,6].…”
Section: Introductionmentioning
confidence: 99%